Radio Frequency Identification (RFID) Based Cable Detection System - Hasan, Syahzani Arifah; Ngajikin, Nor Hafizah; Yaacob, Maslina; Ali, Siti Hajar Aminah; Cholan, Noran Azizan (Evolution in Electrical and Electronic Engineering, 2021)
Cable theft issues have been known worldwide in the past years therefore this paper discusses how to overcome them by using radio frequency identification (RFID) technology in which the RFID reader can detect the unique identifier (UID) number of the RFID tag that is attached on the cable. The main objective is to develop the RFID-based cable detection system using both software and hardware. Additionally, this system will analyze how the voltage received by the reader can be affected when the distance between tag and reader is varied. The system is developed by using RFID RC522 and Arduino UNO as the main components. The RFID reader will read the data from the RFID tag and will be sent to the Arduino UNO for processing according to the codes that have been programmed into the Arduino UNO. Once processed, the OLED display will display the RFID tag’s unique identifier number along with the location of the cable. The range analysis is done by analyzing the distance between reader and tag and the voltage received by the reader. From the results obtained, the trend of range analysis shows that the nearer the distance, the higher the voltage received by the reader. In summary, the proposed solution to the cable theft issues which is RFID based cable detection system could improve the user’s management by reducing the user’s time to locate the cable. However, the system can be improvised by developing a system with the detection range between reader and tag that can reach up to 1m and above.